2009
DOI: 10.1111/j.1525-1594.2009.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Human Clinical Fitting Study of the DexAide Right Ventricular Assist Device

Abstract: The DexAide right ventricular assist device (RVAD) has been developed as an implantable RVAD. The purpose of this study was to determine the final design and optimal anatomical placement of the DexAide RVAD when implanted simultaneously with either of two commercially available left ventricular assist devices (LVADs) in patients. A mock-up DexAide RVAD was used to assess configuration with each of two types of commercially available LVADs at the time of LVAD implantation in three human clinical cases. The pump… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Our DexAide CFRVAD human cadaver and intra-operative fitting studies suggested that the optimum placement of the CFRVAD pump is in the right chest cavity (Figure 2B) when implanted in conjunction with an LVAD (2223). This placement will require a right-angled inlet cannula that runs parallel to the diaphragm on the ventral side of the inferior vena cava and angles cranially to cannulate the diaphragmatic surface of the RV.…”
Section: Lesson Learned In Design and Animal Testing Of A Permanent Imentioning
confidence: 94%
“…Our DexAide CFRVAD human cadaver and intra-operative fitting studies suggested that the optimum placement of the CFRVAD pump is in the right chest cavity (Figure 2B) when implanted in conjunction with an LVAD (2223). This placement will require a right-angled inlet cannula that runs parallel to the diaphragm on the ventral side of the inferior vena cava and angles cranially to cannulate the diaphragmatic surface of the RV.…”
Section: Lesson Learned In Design and Animal Testing Of A Permanent Imentioning
confidence: 94%
“…18 The DexAide RVAD was developed by modifying the CorAide device and has a diameter, length, weight, and device displacement volume of 44 mm, 48 mm, 280 g, and 69 mL, respectively. 51 The implantable centrifugal RVAD was developed by reducing the size of each primary vane, decreasing the number of primary vanes from seven to five and redesigning the volute. The DexAide can pump at speeds ranging from 1800 to 3600 RPM to provide over 5 L min 21 cardiac output to the pulmonary circulation.…”
Section: Coraide/dexaidementioning
confidence: 99%
“…Outflow graft luminal thickening was eliminated by switching to Gortex polytetrafluoroethylene (PTFE) graft (57)(58)(59). The anatomical fitting studies have confirmed the DexAide (Cleveland Clinic) can fit well in conjunction with an implanted LVAD in the right thoracic cavity (60,61). Potential issues caused by the adhesion between the DexAide pump (Cleveland Clinic) and the surrounding organs could be solved with proper wrapping technologies (61).…”
Section: Dexaide Rvad (Cleveland Clinic)mentioning
confidence: 99%